A 324-years temperature reconstruction from Pinus latteri Mason at highland in Chiang Mai Province, Thailand - Pichit Lumyai; KRITSADAPAN PALAKIT; KHWANCHAI DUANGSATHAPORN; KOBSAK WANTHONGCHAI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lumyai P, Palakit K, Suangsathaporn K, Wanthongchai K. 2020. A 324-years temperature reconstruction from Pinus latteri Mason at highland in Chiang Mai Province, Thailand. Biodiversitas 21: 3938-3945.  The objective of this study was to investigate the relationship between the growth of Pinus latteri and climate data in Chiang Mai Province, Thailand. Dendrochronological techniques were used to analyze 35 sample cores. The cross dated ring width data could be extended back for up to 324 years (1692-2015). The relationship between ring-width index and climate data indicated a significant correlation (p < 0.01) with the monthly rainfall in January, monthly temperature in August and September, extreme maximum temperature in August and mean maximum temperature in March and August. The reconstructed average monthly temperature in August was estimated at around  27.35 °C, a warming period could have occurred in 1694-1702, 1834-1844, 1848-1866, 1873-1876, 1884-1890, 1896-1902, 1911-1927, 1942-1958, and 1986-1990, with cooling periods occurring in 1703-1722, 1739-1752, 1865-1872, 1877-1883, 1891-1895, 1903-1910, 1928-1941, 1959-1961, and 1968-1970, which could explain the high fluctuations in temperature. Periods in the range 2.1-2.5, 10.1 , and 13.5 years were found to be common with the variations in  El Niño-Southern Oscillation. In conclusion, the pine growth information can be used to monitor the variations in climate in Thailand.